2017
DOI: 10.1172/jci91363
|View full text |Cite|
|
Sign up to set email alerts
|

The U2AF1S34F mutation induces lineage-specific splicing alterations in myelodysplastic syndromes

Abstract: Mutations of the splicing factor–encoding gene U2AF1 are frequent in the myelodysplastic syndromes (MDS), a myeloid malignancy, and other cancers. Patients with MDS suffer from peripheral blood cytopenias, including anemia, and an increasing percentage of bone marrow myeloblasts. We studied the impact of the common U2AF1S34F mutation on cellular function and mRNA splicing in the main cell lineages affected in MDS. We demonstrated that U2AF1S34F expression in human hematopoietic progenitors impairs erythroid di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
92
1
8

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(109 citation statements)
references
References 67 publications
8
92
1
8
Order By: Relevance
“…These recipient mice also exhibited increase in bone marrow megakaryocytes. However, the U2AF1 mutations induced defects in the lineage populations are not as impactful and appear to be distinct from those reported in other studies using knock‐in mice and human CD34 + model system . These variations could be caused by the differences in culture conditions including the presence of serum, stroma, and combinations of cytokines.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…These recipient mice also exhibited increase in bone marrow megakaryocytes. However, the U2AF1 mutations induced defects in the lineage populations are not as impactful and appear to be distinct from those reported in other studies using knock‐in mice and human CD34 + model system . These variations could be caused by the differences in culture conditions including the presence of serum, stroma, and combinations of cytokines.…”
Section: Discussionmentioning
confidence: 55%
“…These variations could be caused by the differences in culture conditions including the presence of serum, stroma, and combinations of cytokines. The study by Yip et al used separate cultures for granulo‐monocytic and erythroid differentiation . In their study, U2AF1‐S34F was found to skew differentiation toward granulocytes in granulo‐monocytic cultures and cause a block in differentiation in erythroid cultures.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…U2AF1 ‐ S34F impaired erythroid differentiation and reduced growth of erythroid progenitors in human haematopoietic progenitors. Expression of U2AF1‐S34F in human haematopoietic progenitors leads to the skewing of granulo‐monocytic differentiation towards granulocytes . Different phenotypes were observed in ex vivo cultures of primary human CD34 + cells model, U2AF1 mutations (S34F, Q157R) skew granulo‐monocytic differentiation towards monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Reports on analysis of MDS patients have revealed a high incidence of U2AF1‐S34F missense mutation . The study shows that overexpression of this U2AF1‐S34F mutant impairs erythroid differentiation and skews granulomonocytic differentiation towards granulocytes in human haematopoietic progenitors . Depletion of U2AF1 affects the alternative splicing of the Dscam gene transcript in Drosophila .…”
Section: Introductionmentioning
confidence: 92%